A new experimental setup for time- and laterally-resolved X-ray absorption fine structure spectroscopy in a 'single shot'. Issue 1 (14th December 2018) - Kulow, A.; Witte, S.; Beyer, S.; Guilherme Buzanich, A.; Radtke, M.; Reinholz, U.; Riesemeier, H.; Streli, C.
Abstract : A new, simple and adjustable setup allows scanning-free XAS for time-resolved studies of structural changes in chemical compounds. Abstract : In this work, a new setup for dispersive XAFS measurements is presented. This reproducible and scanning-free setup yields both time- and laterally-resolved XAFS experiments in a 'single-shot'. It allows a straightforward adjustment for probing different elements covering many relevant applications in materials science. An incoming energetic broadband beam is diffracted by a Si (111) crystal after passing through the sample and collected by an area sensitive detector. Depending on the energy range of the incoming beam, XANES and/or EXAFS spectra can be recorded with a time resolution down to 1 s. The feasibility of this setup was demonstrated at the BAM line at BESSY II (Berlin, Germany) with reference Fe and Cu foils and the results are hereby presented and discussed. Additionally, an application where time resolution on the second scale is required is briefly evaluated. The presented example concerns studying early stages of zinc(ii )2-methylimidazolate (ZIF-8) crystallization. This is particularly important for biomedical applications.